A bibliometric analysis of the 100 most-cited articles on curcumin - Zhou, Yan-Xi; Cao, Xiao-Yu; Peng, Cheng (Frontiers in Pharmacology, 2022)
Background: Extensive studies related to curcumin were carried out over the preceding several decades. Citation frequencies represent the most prominent contributions in a specific field. This research aimed to identify and analyze the 100 most-cited articles on curcumin and to highlight the most important advances in this field. Methods: Highly cited articles were identified in the Web of Science core collection database. “curcumin*” was used as the search string to retrieve in the “Title” field. VOSviewer was applied to perform bibliometric analysis of these papers. Results: Totally 17,645 publications on the topic of curcumin were identified. The top most-cited 100 articles were published between 1973 and 2017. Most of these papers were original (n = 62). The total citation frequency in the top 100 article ranged from 355 to 3364,with a median of 560. The USA and India were the major countries researching curcumin. The University of Texas M.D. Anderson Cancer Center was the institution with the highest contribution rate of these articles. The most frequently nominated author was Aggarwal BB, and of the top 100 articles, 26 listed his name. The top 100 articles were published in 68 journals. The top four journals in terms of the number of our included articles were Cancer Research (n = 7), followed by Journal of Biological Chemistry, Biochemical Pharmacology, and Cancer Letters, with 4 articles each. NF-kappa B and cancer appeared more frequently in keywords. Conclusion: This study analyzed the 100 most-cited articles on curcumin and provided insights into the characteristics and research hotspots of the articles on this topic.